An Analysis of the Determinants of Community Participation in Sharia Insurance in North Padang Lawas Regency - Lili Cahayani Hasibuan; Isnaini Harahap; Andri Soemitra (Institut Agama Islam Sunan Giri Ponorogo, 2026)
This study aims to analyze the determinants of community participation in Islamic insurance (takaful) in Padang Lawas Utara Regency. The factors examined include Islamic financial literacy, trust, socioeconomic conditions, access to information and socialization, education level, and geographical conditions. This study employed a quantitative approach involving 32 questionnaire indicators. The sample consisted of 160 respondents, determined using a ratio of five respondents for each indicator (32 × 5), which is considered adequate for multivariate analysis. Data were collected through likert-scale questionnaires and analyzed using multiple linear regression with SPSS. The results indicate that all independent variables have a positive and significant effect on community participation, both partially and simultaneously. Geographical conditions are the most dominant variable, with Beta = 0.275 and t = 4.517. Simultaneously, the six variables explain 76.7% of the variation in community participation (R² = 0.767; F = 84.007; Sig. 0.000). This study recommends improving islamic financial literacy, expanding digital-based services, and strengthening infrastructure in remote areas to increase community participation in Islamic insurance in padang lawas utara regency.